Analisis Tahapan Perkembangan Kognitif Anak Usia Dini dan Sekolah Dasar dalam Pembelajaran Berbasis Proyek - Ummaroch, Riza; Restian, Arina; Aimmatu Rosyida, Nuzla; Hasunah, Uun; Arifah, Nurul (J-SES : Journal of Science, Education and Studies, 2025)
This study aims to analyze the suitability between the cognitive developmental stages of Early Childhood Education (ECE) and Primary School students with the implementation of Project-Based Learning (PBL). The research objective is to examine how PBL effectively develops critical thinking, problem-solving skills, and the mastery of basic concepts. The research method employed is a qualitative descriptive literature review, synthesizing findings from relevant studies published between 2020-2025. The results indicate a high alignment between PBL and both the pre-operational (ECE) and concrete operational (Primary) stages. For ECE, the hands-on nature of projects enhances symbolic ability and simple problem-solving. For Primary students, the structured inquiry and application of concepts in real contexts significantly develop logical reasoning and analytical skills. The conclusion suggests that PBL is a developmentally appropriate pedagogical strategy to stimulate higher-order cognitive abilities, transforming students into active knowledge constructors.